Visual Perception and Cognition by the Means of Interactive Digital Replicas of Museum Artifacts: Leonardo da Vinci’s Drawings as If They Were in Visitors’ Hands - Simone Garagnani; Rossella D’Ugo; Andrea Lupi; Berta Martini; Marta Salvucci; Mirko Susta; Monica Tombolato; Roberta Barsanti (Heritage, 2022)
Technologies and applications developed to assist and promote museum activities and cultural exhibitions have evolved significantly during the last decade, as has been proven by many works published in the scientific literature. This paper addresses a study developed with the specific purpose of understanding the possible knowledge-transfer outcomes of a digitization process meant to replicate original drawings by Leonardo da Vinci in the digital domain, allowing museums’ visitors to explore them as if they were manipulating the original artworks through custom interactive artifacts. A report is presented here to evaluate and investigate the didactic effectiveness of the fruition devices set up during a real exhibition, with a focus on the application dedicated to the drawing Study for the Adoration of the Magi, part of five artworks by Leonardo selected for exhibition during the reported event. The results encourage the adoption of this kind of technology for disseminating information at different levels, especially when knowledge contents are successfully explicated through proper didactic mediators.